Charlie Brown's 'cyclopedia: Super Questions and Answers and Amazing Facts: Volume 11: Featuring What We Wear - Charles Monroe Schulz (USA United Feature Syndicate, Inc. Random House, 1980)
Each volume deals with a different subject, such as astronomy, holidays, machines, clothing, transportation, and other scientific subjects. Uses questions and answer format.
Charles Monroe Schulz 1922-2000
Based on The Charles M. Schulz Characters . Distributed by Funk & Wagnalls
LC has v. 1-4 and 6-15 only. c1980-<c1981 > . v. <1-4, 6-15 > (720 p.) : col. ill.
Keywords: Encyclopedias (3GdehShYGJs; Children's encyclopedias and dictionaries; General; Encyclopedias and dictionaries; Science -- Dictionaries; Questions and answers